2023
DOI: 10.3390/su15118915
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Curriculum Reform Based on Outcome-Based Education and Five-Color Psychology Theory

Abstract: Innovation in curriculum design at the system level is crucial for nurturing students’ sustainability skills. This study focuses on the teaching reform of a hydraulic engineering construction and management course, taking a sustainable development perspective and achieving a harmonious integration of knowledge acquisition and skill development. A “One Center, Two Platforms, and Three Education” teaching model is devised, incorporating outcome-based education and five-color psychological theory. This model enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…This result justifies the studies of Gurukkal (2020) and Posecion (2015) that OBE excels in providing learners with the necessary tools and skills to develop new knowledge through critical thinking and problem solving. The findings also conform to the idea of De Boer et al ( 2018) and Hu et al (2023) that OBE effectively incorporates a student-centered approach and teachers' higher expectations lead to positive students learning. Additionally, it proves that in open and distance learning, OBE can be an effective restructuring tool for identifying authentic learning outcomes, assessments and teaching and learning activities.…”
Section: The Level Of Agreement On the Effectiveness Of Outcome-based...supporting
confidence: 88%
See 1 more Smart Citation
“…This result justifies the studies of Gurukkal (2020) and Posecion (2015) that OBE excels in providing learners with the necessary tools and skills to develop new knowledge through critical thinking and problem solving. The findings also conform to the idea of De Boer et al ( 2018) and Hu et al (2023) that OBE effectively incorporates a student-centered approach and teachers' higher expectations lead to positive students learning. Additionally, it proves that in open and distance learning, OBE can be an effective restructuring tool for identifying authentic learning outcomes, assessments and teaching and learning activities.…”
Section: The Level Of Agreement On the Effectiveness Of Outcome-based...supporting
confidence: 88%
“…The effectiveness of this method of instruction has received positive feedback from both graduates and employers who recognised its commitment to improving teaching quality and promoting long-term educational growth. Furthermore, this model can be used to improve college education by developing students' abilities and ethical standards (Hu, Mao, Fu, Wu, & Zhou, 2023).…”
Section: Teaching and Learning Activitiesmentioning
confidence: 99%
“…Traditionally focused on theoretical knowledge, the engineering education claims for innovative teaching methods integrating sustainability into engineering education (Hu et al, 2023). Several Stakeholders are unanimous in the need for an engineering curriculum that focuses on change, the creation and addition of value and the development of transversal skills in engineering training.…”
Section: The Curriculum: Change Values and Skills Matchmentioning
confidence: 99%
“…Undergraduate education is required to equip students with the skills to solve interdisciplinary engineering challenges across technical and nontechnical boundaries, communicate and transfer knowledge. To train engineers in these skills, one of the proposed approaches is to teach design inspired by an engineering curriculum, which offers relevance to professional practice, as well as to frame complex and interdisciplinary problems (Najdanovic-Visak, 2017;Nagel et al, 2019a,b;Trevelyan and Williams, 2019;Hu et al, 2023). Camargo Ribeiro and Mizukami (2005) and Heywood (2005) recognized that an engineering curriculum integrating the liberal arts would be highly relevant for the training of future engineers, as it would provide for the development of professional competences and attitudes that are indispensable to their practice, such as autonomous and lifelong learning, critical thinking, initiative, creativity, teamwork skills, responsibility toward society and their profession, entrepreneurship and ethics.…”
Section: Challengesmentioning
confidence: 99%
“…Hu et al pointed out that innovation in curriculum design at the system level is crucial for cultivating the sustainable development skills of students; they combined the results of education and the theory of five colors in psychology to reform the teaching of hydraulic engineering construction and management courses. The results showed that this model holds reference significance for strengthening higher education and cultivating abilities and moral standards [11]. Ruslan et al discussed the application of an integrated project-based learning (IPBL) method to help students integrate knowledge gained from one course into another and demonstrated the effectiveness of the method through the production of hydraulic jacks [12].…”
Section: Introductionmentioning
confidence: 99%